Candidate genes polymorphisms in smoking behavior among malay population - Bakar, Ruzilawati Abu
Smoking behavior is influenced by both genetic and environmental factors. Genetic variables appear to play a key role in every aspect of nicotine addiction. Nicotinic acetylcholine receptors (nAChRs), dopamine receptors (DR) as well as serotonin receptor, 5-HT2A and serotonin transporter, 5-HTT are thought to play an important role in nicotine addiction of smokers. The objectives of this study was to examine the frequency of single nucleotide polymorphisms in the CHRNA4 genes (rs2273502 and rs2236196), dopamine receptors (DR), the 5-HT2A serotonin receptor and serotonin transporter, 5-HTTLPR genes among Malay smokers. The study was conducted in 248 Malay smokers and 248 Malay non-smokers. DNA was extracted from leucocytes and the allele was determined by a polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP). The PCR product was digested with restriction enzymes. Our result suggested that the CHRNA4 (rs2273502 and rs2236196), DR, 5-HT2A and 5HTTLPR gene polymorphisms are not major determinants of smoking behavior in Malay populations